The influence of tumour fluorodeoxyglucose avidity and cachexia development on patient survival in oesophageal or gastroesophageal junction cancer. Issue 4 (5th September 2021) - Olaechea, Santiago; Gannavarapu, Bhavani S.; Gilmore, Anne; Alvarez, Christian; Iyengar, Puneeth; Infante, Rodney
Abstract: Background: Cancer cachexia is manifested by loss in muscle, adipose, weight, and appetite. PET 18 F‐FDG uptake identifies tumour metabolic and inflammatory changes, potentially associated with cachexia development. We examined if primary gastroesophageal tumour 18 F‐FDG uptake correlates with cachexia development and survival in cancer patients. Methods: One hundred twenty‐six oesophageal ( n = 87) and gastroesophageal junction ( n = 39) cancer patients, with a median age at diagnosis of 63 years (IQR 54–71), evaluated between 2006 and 2014 with pre‐treatment PET imaging and cachexia determination at diagnosis were included in the study cohort (22.1% female; 6.7%, 24.4%, 50.4%, and 18.5% with tumour stage I, II, III, and IV, respectively). Maximum primary tumour standardized uptake values were obtained and dichotomized based off the calculated cut‐point SUVMax of 8.5 ( P = 0.0018). Associations between survival, cachexia development, and primary tumour 18 F‐FDG uptake were evaluated using univariate and multivariate analyses. Results: Cancer‐associated weight loss (cachexia) and primary tumour SUVMax at or above the statistically determined cut‐point of 8.5 were present in 54% and 57% of patients, respectively. Primary tumour SUVMax above the cut‐point was significantly associated with pre‐treatment cancer‐associated weight loss ( P = 0.0033) and, in multivariate analysis, correlated with a 2.3‐fold increased risk of death (95% CI 1.4, 3.7; P = 0.0010). When divided into cohorts defined by their combined cachexia and high versus low SUVMax tumour status, positive cachexia status or/and high SUVMax tumours were associated with similar significant decrements in survival. Conclusion: A positive association was present between cancer‐associated weight loss and SUVMax of the primary tumour, suggesting greater glycolytic metabolism in gastroesophageal tumours that induce cachexia. This interpretation of routinely administered PET scans could lead to earlier categorization of patients with cachexia‐inducing tumours. Both cachexia and high SUVMax status were independently associated with worsened survival outcomes, further supporting their prognostic relevance in patients with gastroesophageal cancer.